Heterogeneity in consumers' perceptions and demand for local (organic) food products. (April 2019) - Jensen, Jørgen Dejgård; Christensen, Tove; Denver, Sigrid; Ditlevsen, Kia; Lassen, Jesper; Teuber, Ramona
Highlights: Danish consumers mainly understand local food in terms of geographical proximity. Local food associated with small and enthusiastic producers and regional specialties. Five consumer clusters identified – three with emphasis on organic or local food. Potential for value-added in enhanced geographic differentiation of organic food. Abstract: "Local" is becoming increasingly important in consumers' food purchase decisions. Perceived benefits of local foods are rather similar to those of organic products, including aspects of taste, food safety, animal welfare and reduced environmental impacts. Yet, only limited knowledge is available regarding different consumers' conceptualization of local food. Our study addresses this research gap by investigating organic versus non-organic consumers' perceptions of local foods and these perceptions' association with purchasing behaviour. A mixed-methods approach was employed, combining eight focus group interviews (52 participants in total) with a representative survey of 1515 Danish consumers. Focus group interviews revealed that Danish consumers mainly understand local food in terms of geographical parameters, such as "nationally produced", or "produced nearby". Besides this geographical component, focus group participants' perceptions of localness were relatively vague, although certain connotations could be identified, such as the association with small and enthusiasm-driven producers, regional specialties and the story-telling around local products. Five clusters of consumers were identified from the questionnaire data. Three clusters had specific profiles in relation to purchasing organic or local food products: a "Local" (31% of the sample), an "Organic" (19% of the sample), and an "Organic-Local" (7% of the sample) cluster. These consumers are relatively prone to consider local foods as produced nearby and to consider relational aspects in their conceptualization of local products, but they also differ in their orientation towards local and organic purchases, respectively. These findings suggest a stronger role for geographic differentiation to increase value-added in organic food products.